2009
DOI: 10.1007/s11814-009-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification and adsorption of eucalyptus wood-based activated carbons: Effects of oxidation treatment, carbon porous structure and activation method

Abstract: The incorporation of oxygen functional groups onto the surface of eucalyptus activated carbon and its surface chemistry were investigated as a function of oxidation conditions, carbon porous properties and carbon preparation method. Under all treatment conditions of increasing time, temperature and oxidant concentration, liquid oxidation with HNO 3 , H 2 O 2 and (NH 4 ) 2 S 2 O 8 and air oxidation led to the increase of acidic group concentration, with carboxylic acid showing the largest percentage increase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…The slight decrease in AC 1 surface area may be due to the abundant presence of oxygen-containing groups introduced on the surface of the activated carbon by treatment with HNO 3 , which possibly block the entry of N 2 inside the small pores. After treatment at 900°C (sample AC 1tt900 ), the mentioned functional groups were removed by thermal decomposition and the area of the corresponding support increased slightly comparatively to the original carbon [24,25]. The textural parameters of the Pd/AC 0 catalyst decreased only slightly compared to the unloaded carbon.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…The slight decrease in AC 1 surface area may be due to the abundant presence of oxygen-containing groups introduced on the surface of the activated carbon by treatment with HNO 3 , which possibly block the entry of N 2 inside the small pores. After treatment at 900°C (sample AC 1tt900 ), the mentioned functional groups were removed by thermal decomposition and the area of the corresponding support increased slightly comparatively to the original carbon [24,25]. The textural parameters of the Pd/AC 0 catalyst decreased only slightly compared to the unloaded carbon.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…Tangsathitkulchai et al (2009) reported that liquid oxidation with the sulphuric acid led to an increase in acidic group concentration, with carboxylic acid normally showing the largest percentage increase. Tangsathitkulchai et al (2009) subsequently found that the increased contents of acidic groups on oxidized carbons greatly enhanced the adsorption capacity of heavy metal ions. In this study, the treatment of the native wood chips with sulphuric acid would most plausibly have produced oxidized carbons.…”
Section: Fourier Transform Infrared (Ftir) Analysis Of Adsorbentsmentioning
confidence: 99%
“…However the ACP-HNO3 is oxidized with nitric acid (which is milder than H2O2), the micropore volume is barely affected and the concentration of the functional group is increased by 50% as shown in Table 3. The reduction in surface area and pore volume of oxidized carbons, especially ACC-H2O2, is due to an inaccessibility of the probe molecules into the pore interior caused by the oxidation reaction between oxidizing agent and unstable covalent bond between carbons, leading to the partial collapse of pore walls [36].…”
Section: Adsorption Of Water In Activated Carbonmentioning
confidence: 99%